Study of deuterium permeation, retention, and desorption in SiC coatings submitted to relevant conditions for breeder blanket applications: thermal cycling effect under electron irradiation and oxygen exposure - Hernández Díaz, Teresa (Journal of Nuclear Materials, 2021)
In this paper we report on the performance as deuterium permeation barriers of sputtered amorphous, dense and not fully stoichiometric SiC coatings under relevant conditions for breeder blanket applications in fusion reactors. To do that, we investigate the following effects on permeation values: (i) thermal cy- cling at 450 °C, (ii) combined thermal cycling and e −irradiation (1.8 MeV up to a total dose of 1 MGy), as well as (iii) oxygen exposure at a temperature of 450 °C during e −irradiation. Data show that the permeation reduction factor (PRF) for the as-deposited SiC coated is ∼10 4 , even at the predicted opera- tion temperature for the breeder and it is slightly reduced either by thermal cycling without and during e −irradiation. However, the exposure to oxygen at 450 °C during e −irradiation leads to degradation of the coating and of its PRF of about three orders of magnitude. The origin of the coating degradation is discussed. We also study the D retention and desorption in SiC coatings that were implanted with D at energy of 7.5 keV prior to (as-deposited) and after being submitted to the treatments previously described. Sec- ondary ion mass spectroscopy data show that thermal cycling, without and during e −irradiation, strongly increases the D retention in the coatings and leads to the appearance of D 2 desorption peak at temper- atures between ∼400-750 °C, whereas e-irradiation during thermal cycling does not significantly change the D retention but shifts to higher temperatures thisD 2 desorption peak
Keywords: SiC coating; tritium permeation